Screening Buccal Smear to Identify Cytological Alterations Brought on by Hormone Therapy - Fadwa Mohammed Ebraheem; Alkhair Abd Almahmoud Idris; Mudather Elnoor Younis (International Journal of Health and Social Behavior, 2024)
Objective: To assess the differences in buccal cytology changes caused by hormone therapy in Sudanese women with breast and endometrial malignancies by comparing wet fixed and air dry H&E stained buccal smear samples.  Method: The eight-month study period ran from October 2015 to May 2016. The practical inquiry began in November 2015, and during that time, data gathering, a literature review, and research script typing were completed. One hundred participants had buccal smear samples taken, and these were ready for H&E staining using a wet and dry procedure on women receiving hormone medication. Results: The wet method produced buccal smears with pathology that was 56% malignant, 34% inflammatory, and 10% normal; the dry method produced identical results. The wet method produced excellent (40%), very well (28%), well (20%), acceptable (8%) and bad (4%) affinity, which was in line with the results of the dry method. There were no appreciable variations in the pathology and affinity of the wet and dry-prepared buccal smears (P = 0.14 and 0.0011 > 0.05). The cancerous The pathology of wet and dry buccal smears was reported in 7.7%, 47.1%, and 95% of the smears obtained from patients who had been on hormonal therapy for less than three years, three to nine years, and more than nine years, respectively. Wet and dry smears were reported in 20%, 21.1%, and 88.5% of the smears obtained from patients who had been on hormonal therapy once, twice, or three times a day, respectively. Conclusion: The pathology of the buccal smears showed significant differences based on the frequency and duration of hormone therapy.